2022
DOI: 10.1242/jcs.258991
|View full text |Cite
|
Sign up to set email alerts
|

SAF-A promotes origin licensing and replication fork progression to ensure robust DNA replication

Abstract: The organisation of chromatin is closely intertwined with biological activities of chromosome domains, including transcription and DNA replication status. Scaffold attachment factor A (SAF-A), also known as Heteronuclear Ribonucleoprotein Protein U (HNRNPU), contributes to the formation of open chromatin structure. Here we demonstrate that SAF-A promotes the normal progression of DNA replication, and enables resumption of replication after inhibition. We report that cells depleted for SAF-A show reduced origin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 84 publications
4
9
0
Order By: Relevance
“…The results of our transcriptional profiling showed a role of HNRNPU in chromatin organization, in line with previous reports that demonstrated the function of HNRNPU in chromatin compaction, DNA synthesis, and chromosome folding during mitosis in different cell types and conditions (Connolly et al, 2022; Nozawa et al, 2017; Sharp et al, 2020). Therefore, we sought to investigate whether HNRNPU deficiency affects chromatin organization in our human neural cell model.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The results of our transcriptional profiling showed a role of HNRNPU in chromatin organization, in line with previous reports that demonstrated the function of HNRNPU in chromatin compaction, DNA synthesis, and chromosome folding during mitosis in different cell types and conditions (Connolly et al, 2022; Nozawa et al, 2017; Sharp et al, 2020). Therefore, we sought to investigate whether HNRNPU deficiency affects chromatin organization in our human neural cell model.…”
Section: Resultssupporting
confidence: 92%
“…Here, we provide novel evidence of the molecular and cellular consequences of HNRNPU deficiency in human neuronal cells, demonstrating that adequate levels of HNRNPU are needed in the early developmental transition from neural progenitors to developing neurons for proper neurogenesis. Our results, consistent with the earlier reports, show that HNRNPU expression is highest at early neural stem cell and progenitor stages and in a subpopulation of neural progenitors at the later stage of neuronal differentiation (Connolly et al, 2022; Sapir et al, 2022). Despite this high expression, results indicate that HNRNPU deficiency does not affect neural cells at this early stage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Manp localizes exclusively in the nucleus and redirects MLF1 into the nucleus ( 8 ). Recent studies have suggested that hnRNP-U regulates DNA replication, organizes large-scale chromosome structures, and protects the genome from instability ( 39 41 ). The effects of MLF on DNA synthesis have been previously discussed ( 19 ).…”
Section: Mlf1 Networkmentioning
confidence: 99%
“…Knockdown of the protein led to increased spacing between replication origins, slowing the replication fork progression, creating replication stress, and increasing cellular quiescence. [ 47 ] Shortly after exposure to ionizing irradiation and induction of double strands breaks, HNRNPU/SAF‐A transiently clusters at damage sites. This localization is regulated by phosphorylation at Ser59 by (DNA‐dependent protein kinase) DNA‐PK, thus suppressing base excision repair (BER) initiation and allowing the predominant nonhomologous end joining (NHEJ) repair to proceed.…”
Section: Hnrnpu/saf‐a a Regulator Of Chromatin Organizationmentioning
confidence: 99%